Size- and Shape-Dependent Clinical and Mycological Efficacy of Silver Nanoparticles on Dandruff [Corrigendum] - Anwar M; Yadav D; Jain S; Kapoor S; Rastogi S; Arora I; Samim M (International Journal of Nanomedicine, 2021)
Anwar M, Yadav D, Jain S, et al. Int J Nanomedicine. 2016;11:147–161. The authors have advised due to an error at the time of figure assembly, Figure 4A on page 156 is incorrect. The correct Figure 4 is shown in Download Article. The authors apologize for this error and advise it does not affect the results of the paper. Read the original article